Revolutionizing Global Business Excellence Through the Balanced Scorecard Success: Merevolusi Keunggulan Bisnis Global Melalui Keberhasilan Balanced Scorecard - Ula, Adinda Lafilatul; Fitriyah, Hadiah (Indonesian Journal of Law and Economics Review, 2024)
This study evaluates PT Berkah Berabu Limpah's performance using the Balanced Scorecard method. It collects qualitative data from primary and secondary sources and analyzes it across Financial, Customer, Internal Business Process, and Learning and Growth perspectives. Results indicate good overall performance but suggest improvements in customer focus and employee training for enhanced competitiveness. Implementing Balanced Scorecard comprehensively is recommended for better performance management. This research contributes to understanding performance evaluation methods for strategic decision-making. Highlight: Integrated Performance Analysis: Evaluates PT Berkah Berabu Limpah holistically using Balanced Scorecard. Customer Centricity Emphasis: Highlights need for enhanced customer focus and satisfaction. Strategic Decision Support: Balanced Scorecard aids in informed, strategic decision-making processes. Keyword: Performance Evaluation, Balanced Scorecard, Qualitative Analysis, Customer Focus, Strategic Decision-making